Penyerlahan identiti, personaliti, dan emosi remaja di facebook - Nor Fazilah, Noor Din (2021)
In the rapid globalization era, the Internet and social media has become a new medium of communication in disseminating information to the public which aids in the formation of one's identity and ethos. Apart from identity, adolescents in Malaysia also face personality disorder on the Internet which makes self-behaviour difficult to identify. At the same time, the influences of virtual interaction environment also affect one’s emotions. In the rapid globalization era, the Internet and social media has become a new medium of communication in disseminating information to the public which aids in the formation of one's identity and ethos. Apart from identity, adolescents in Malaysia also face personality disorder on the Internet which makes self-behaviour difficult to identify. At the same time, the influences of virtual interaction environment also affect one’s emotions. Thus, based on the problems mentioned, three (3) objectives of the study were formulated, namely i) identify the themes of adolescent conversations on Facebook, ii) explain adolescents’ identities, personalities, and emotions that were highlighted based on the conversational themes and iii) describe the use of adolescent language on Facebook and its relation to psychological theory. The present study employs content analysis method with the application of Semantic Prosody Theory (TPS) aimed to examine the expression of a word based on its presence (joined, adjacent, or collocated) with other words through language use among adolescents on Facebook. Subsequently, the findings obtained through the TPS application were referred to three psychological theories, namely Erikson Identity Development Theory (TPIE), Big Five Theory (BFT), and Plutchik Wheel of Emotion Theory (PWoE) to highlight adolescent identity, personality, and emotions on Facebook. The findings of the study demonstrate that the three themes of conversation that teenagers often use on Facebook, are the themes of relationships, economics, and politics. With the help of the three conversation themes, moratorium identity, neuroticism and extraversion personality, as well as emotions of anger and trust in adolescents in Malaysia through the use of language on Facebook was successfully highlighted based on the concept of consistent aura as conceived in the TPS. This study has successfully achieved all the objectives of the study by highlighting aspects of personality, identity, and emotions simultaneously through verbal-written communication (Facebook) based on the application of Virtual Advertising Operations (OPM) method which enabled the description of adolescent language use on Facebook to be explained.